Use of anti-inflammatory agents in clinical islet cell transplants: A qualitative systematic analysis. Issue 3 (4th May 2019) - Szempruch, Kristen R.; Banerjee, Oyshik; McCall, Rebecca C.; Desai, Chirag S.
ABSTRACT: Immunologic and non-immunologic loss of islet cells upon their transplantation into the liver leads to suboptimal outcomes. Anti-inflammatory agents are used during autologous and allogeneic transplantation. The aim of this qualitative systematic literature review is to evaluate their clinical use and safety. Electronic databases Embase, PubMed, Cumulative Index for Nursing and Allied Health Literature, ClinicalTrials.gov, and EU Clinical Trials Register were searched. Of the 216 unique citations, 10 with tumor necrosis factor (TNF) blockers [etanercept (ETA) or infliximab] and 3 with both TNF blockers and an interluekin-1 receptor antagonist [anakinra (ANA)]) were included. Of these, 12 were in allogeneic and one in autologous transplant. Insulin independence with decreased islet cells and number of transfusions were reported with their use. One infection was reported in a group receiving ETA. Analysis suggested that the use of ETA ± ANA have the potential to improve outcomes in islet cell transplant.